The fighting Sullivans [videorecording (DVD)] - Bacon, Lloyd, 1890-1955; Baxter, Anne; Mitchell, Thomas, 1892-1962; Royle, Selena, 1904-1983 (VCI Entertainment, 2005)
The five Sullivan brothers were close since their childhood in Iowa. They went to war together and all five died together when their ship, the U.S.S. Juneau, was sunk in the Pacific.